2012
DOI: 10.1103/physreve.86.021126
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of dipolar hard spheres with low-to-intermediate coupling constants

Abstract: The thermodynamic properties of the dipolar hard-sphere fluid are studied using theory and simulation. A new theory is derived using a convenient mathematical approximation for the Helmholtz free energy relative to that for the hard-sphere fluid. The approximation is designed to give the correct low-density virial expansion. New theoretical and numerical results for the fourth virial coefficient are given. Predictions of thermodynamic functions for dipolar coupling constants λ=1 and 2 show excellent agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…In Ref. [24] it was shown that the LFE expressions containing expansions of B 2 , B 3 , and B 4 in terms of λ are superior to the traditional TPT results [22,23] for DHS fluids with λ 4 and ρσ 3 0.95.…”
Section: B Virial Coefficients For Dhss In An Applied Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…In Ref. [24] it was shown that the LFE expressions containing expansions of B 2 , B 3 , and B 4 in terms of λ are superior to the traditional TPT results [22,23] for DHS fluids with λ 4 and ρσ 3 0.95.…”
Section: B Virial Coefficients For Dhss In An Applied Fieldmentioning
confidence: 99%
“…In Ref. [24], a new theory was developed from a logarithmic representation of the Helmholtz free energy F . For the case of DHSs in an applied field, this theory is based on the relation…”
Section: B Virial Coefficients For Dhss In An Applied Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…As the system is cooled down, 0.5 ≥ T ≥ 0.2, particles start to self-assemble into small, disordered clusters. 37 At this T, thermal fluctuations are so relevant that the formed clusters do not have a clear chain-like shape and contain many defects. In this regime, defect cluster size distributions are monotonic and do not have any of the features found at low temperatures.…”
Section: A Identification Of the Defect Clusters And Their Spatial Cmentioning
confidence: 99%